2011
DOI: 10.3109/00365548.2011.608082
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a combined oral clindamycin–rifampicin regimen for therapy of staphylococcal osteoarticular infections

Abstract: A majority of osteoarticular and implant-related infections are due to staphylococci and biofilm formation. Combined therapy including rifampicin is frequently recommended. Indeed, rifampicin penetrates biofilms and kills adherent staphylococci, but cannot be administered as monotherapy because of the rapid emergence of resistant mutants. While several antibiotic combinations including rifampicin have been implemented, evaluation of the clindamycin-rifampicin combination has been neglected, presumably because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…It inhibits production of S. aureus toxins (Otto et al 2013), additionally to the exhibition of its antibacterial activity. Combination of clindamycin with rifampin has also been suggested (Czekaj et al 2011), but recent pharmacokinetic studies demonstrated dramatic reduction of clindamycin serum concentration if combined with rifampin (Bernard et al 2015a;Join-Lambert et al 2014). Therefore, caution is recommended regarding this combination until more data become available.…”
Section: Antimicrobial Treatmentmentioning
confidence: 99%
“…It inhibits production of S. aureus toxins (Otto et al 2013), additionally to the exhibition of its antibacterial activity. Combination of clindamycin with rifampin has also been suggested (Czekaj et al 2011), but recent pharmacokinetic studies demonstrated dramatic reduction of clindamycin serum concentration if combined with rifampin (Bernard et al 2015a;Join-Lambert et al 2014). Therefore, caution is recommended regarding this combination until more data become available.…”
Section: Antimicrobial Treatmentmentioning
confidence: 99%
“…In vitro, clindamycin prevents the emergence of rifampin resistance, and the combination displayed synergetic or additive bactericidal activity, as well as favorable cure rates in animal models [1318]. To date, only 2 case series have reported on the efficacy of an oral clindamycin-rifampin combination therapy regimen for staphylococcal PJI in adults, with a success rate of 70% in 7 cases and 100% in 6 cases [6, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, another benefit of combination treatment is the possibility of a synergistic effect between two antibiotics given together. Oral antibiotics proposed for combination therapy with rifampicin in order to reduce the risk of emerging resistance include fluoroquinolones , clindamycin , fusidic acid , trimethoprim‐sulphamethoxazole , and linezolid . It is recommended to avoid combining rifampicin with beta‐lactam or glycopeptide antibiotics, as rapid emergence of resistance to rifampicin has been observed using these combinations .…”
mentioning
confidence: 99%